The expected impact of COVID-19 on the UN Sustainable Development Goal 8 in Hungary based on a survey of trade unions - Riedelmayer, Bernadett; Ásványi, Zsófia; Sipos, Norbert; Barakonyi, Eszter; Galambosné Tiszberger, Mónika (Vezetéstudomány / Budapest Management Review, 2023)
In this study the authors focus on the results of an International Labour Organization (ILO) survey conducted in 2021 for Hungary. The global survey assessed the impact of COVID-19 on trade union leaders’ perceptions of the extent to which it stimulates or hinders the achievement of the Sustainable Development Goal (SDG8) declared by the UN 2030 Agenda. With regard to SDG8’s “Decent Work and Economic Growth”, the views of trade unions as institutions that defend workers’ labour interests are important and decisive, although by no means exclusive. In this research, the authors use a questionnaire survey to investigate the general awareness of Hungarian trade union leaders regarding the SDG8 targets and the impact of COVID-19 on SDG8 implementation at both the national and organisational levels. The authors discuss their findings in comparison with the results of global ILO research and reinforce the professional relevance of the SDGs.